Cellular Oxidative/Antioxidant Balance in γ-Irradiated Brain: An Update - Robello, Elizabeth (2016)
Both epidemiological and experimental data indicate that ionizing radiation (IR) may disrupt developmental processes leading to deleterious effects on brain functions. A central role of reactive oxygen (ROS) and nitrogen species (RNS), as important mediators in neurotoxicity and neuroprotection, has been demonstrated. Primary ionization events triggered by IR are amplified and propagated by mechanisms involving ROS and RNS, which activate several signaling pathways leading to final radiation effects. The immature and adult brain display clear differences in the way they respond to insults. Moreover, a great deal of attention is being focus on the limited antioxidant capacity and the particular lipid composition of cell membranes of the developing brain that render it more vulnerable to oxidative stress. The goal of this review is to summarize the current knowledge on the role of alterations in the balance between oxidative/nitrosative stress and antioxidant capacity in the pathways involved in cellular radiation response, with particular focus on the possible therapies proposed to limit radiation-induced effects in the brain.